Exposição precoce a micotoxinas: o contributo dos projetos MYCOMIX e earlyMYCO - Alvito, Paula (2020)
Artigo baseado no original publicado em: Assunção R, Martins C, Vasco E, Jager A, Oliveira C, Cunha SC, Fernandes JO, Nunes B, Loureiro S, Alvito P. Portuguese children dietary exposure to multiple mycotoxins – An overview of risk assessment under MYCOMIX project. Food Chem Toxicol. 2018;118:399-408. https://doi.org/10.1016/j.fct.2018.05.040